PENGARUH MODAL SOSIAL KOGNITIF TERHADAP PERFORMANSI DUSUNG - Anjely A. Parera; Agustinus Kastanya; Marthina. Tjoa (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
The cognitive social capital of the Murnaten village community in managing dusung includes trust, cooperation, and solidarity-based on norms, values, attitudes, and oriented beliefs in the form of action to strengthen positive efforts in dusung management. This study aims to analyze the effect of cognitive, social capital on the performance of dusung in Murnaten Village, Taniwel District, West Seram Regency. The results showed that the effect of cognitive, social capital (trust, cooperation, and solidarity) on dusung performance (productivity, efficiency, sustainability and fairness with a determinant coefficient value adjusted R2 of 0.771, with F-count (25.359)> F-table (2.759), and the partial test t-count> t-table (2.059) shows that cognitive, social capital (trust, cooperation, and solidarity) has a significant effect simultaneously and partially on dusung performance (productivity, efficiency, sustainability, and justice) at the 0.01 level of confidence. and 0.05.fairness) at the 0.01 and 0.05 confidence levels.